Gambaran Kualitas Tidur Sebelum Sooca Sistem Reproduksi pada Angkatan TA 2021-2022 - Nadia Mufliha Zahro; Ike Rahmawaty Alie; R.Kince Sakinah (Bandung Conference Series: Medical Science, 2023)
Abstract. Lack of quality sleep can have the effect of decreasing concentration, participating in daily activities, and making decisions. Therefore this must be considered because the decrease in the quality of sleep will affect the learning process, impaired memory and emotional health. This study aims to see an overview of sleep quality in Class of 2019, Faculty of Medicine, Bandung Islamic University. The research method is descriptive to see an overview of sleep quality in 2019 Batch students. The sample for this study was taken randomly with a total of 100 people, FK students Batch 2019. The independent variable of sleep quality and the dependent variable is academic achievement. The data analysis used was univariate and bivariate, bivariate analysis. The results showed that the subjective sleep quality was mostly quite poor (46%), sleep latency was mostly 3-4 hours (36%), sleep duration was mostly 5-6 hours (31%), daily sleep efficiency was mostly <65% (84%), sleep disturbance mostly 1-9 (67%), use of sleeping pills mostly never, daytime dysfunction mostly 1-2 hours (43%), and sleep quality scores in FK Unisba students The 2019 batch was mostly unfavorable (99%) while sleep quality was good (1%). Abstrak. Kurangnya kualitas tidur dapat memberikan efek pada penurunan dalam berkonsentrasi,aktifitas sehari-hari dan membuat keputusan. Menurunnya kualitas tidur akan mempengaruhi dari proses belajar, memori terganggu dan kesehatan emosi. Penelitian ini bertujuan untuk melihat gambaran kualitas tidur pada Angkatan 2019 Fakultas Kedokteran Universitas Islam Bandung. Metode penelitian yakni deskriptif untuk melihat gambaran kualitas tidur pada mahasiswa Angkatan 2019. Sampel penelitian ini dilakukan dari bulan Juni sd September sejumlah 100 orang, mahasiswa FK Angkatan 2019, dengan pengambilan sampel secara random sampling. Analisis data yang digunakan adalah univariat dan bivariat, analisis bivariat. Hasil penelitian menunjukkan bahwa kualitas tidur subjektif sebagian besar cukup buruk (46%), latensi tidur Sebagian besar 3-4 jam (36%), durasi tidur Sebagian besar tidur 5-6 jam (31%), efisiensi tidur sehari-hari Sebagian besar <65% (84%), gangguan tidur Sebagian besar 1-9 (67%), penggunaan obat tidur Sebagian besar tidak pernah, disfungsi siang hari sebagian besar 1-2 jam (43%), dan skor kualitas tidur pada mahasiswa FK Unisba Angkatan 2019 sebagian besar kurang baik (99%) sedangkan kualitas tidur baik (1%).